AVERAGE INCOME AND ITS USE IN TAXATION. - Atlas, Martin (The Accounting Review, 1938)
Since the beginning of income-tax legislation in the United States, the concept of the annual accounting period has been accepted per se in the calculation of the income tax. But before entering into a fuller discussion of the concept of the annual accounting period, the article diverges to inquire into the government's aim in levying the tax. Is it to receive as great a yield as possible, or is it to burden each taxpayer equitably according to his ability to pay? If the former is the aim, then the government must be condemned because a much more successful and complete shakedown of the taxpayer is possible; but if the latter is the aim, then the government must be condemned because of the gross inequities that arise from the use of an annual accounting period. Significant to observe is that the use of the annual accounting period does not cause only the taxpayer to be the loser. For the use of such an arbitrary period is equally the cause of diminution in the size of the receipts to the State. The article presents illustrations of both classes of inequities.